THE DEVELOPMENT OF NATIONALISM EDUCATION APPROACHES IN ISLAMIC BOARDING SCHOOLS - Abdurrohim, Abdurrohim; Fitriani, Ely; Fadlillah, Nilna; Abdullah, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The study on nationalism remains a hot topic today, especially in the field of education, which plays a crucial role in shaping the nation's future generations. This includes Islamic boarding schools, currently numbering over 30,000 with more than 4 million students. In Malang Regency alone, there are over 600 pesantrens, signifying the potential impact of students as the nation's future generation and the need to focus on their understanding of nationalism. This is particularly relevant as, in 2016, around 19 pesantrens were suspected of teaching radical ideologies. Therefore, there is a need for strategies to teach nationalism using different approaches. This research utilizes a qualitative descriptive approach with a multi-case study involving three pesantrens: Pesantren Raudlatul Ulum 1, Pesantren Modern Al-Rifa'ie, and Pesantren An-Nur al- Huda. The analysis reveals diverse approaches in the strategies for instilling nationalist values, including integrative, contextual, and collaborative approaches. These involve various activities, ranging from delivering materials on Pancasila and citizenship, studying the Idzatun Nasyiin book, engaging in social service and philanthropy, to participating in national flag ceremonies such as on August 17 and National Santri Day. However, the implementation of these strategies faces challenges, such as a lack of understanding of nationalism, a shortage of discipline among students, and limitations in facilities and infrastructure.